Mental health features in the context of bariatric surgery - Плюта, Ірина; Chaban Олег; Skyba Володимир (Psychosomatic Medicine and General Practice, 2025)
This review of contemporary literature focuses on the mental health features in the context of bariatric surgery. The clinical benefits of bariatric surgical techniques for the physical health of patients with obesity have been well established. However, the psychosocial outcomes of treatment are less evident and require further detailed investigation. It is worth noting that the physical changes following bariatric intervention may lead to the development of stress dominance, anxiety, and depression, the early diagnosis of which can improve the long-term clinical outcomes of bariatric procedures. Psychological support for patients at all stages of bariatric intervention can help them adapt to new life conditions and ensure the long-term clinical effectiveness of the treatment. Psychosocial monitoring of patients after bariatric procedures is considered an integral component of care, as it helps reduce the risk of self-harm and suicide attempts. Although a multidisciplinary team is an essential part of the treatment process, standardized guidelines for psychological support in patients undergoing bariatric surgery are lacking. The development of a personalized approach and early identification of high-risk patients for psychopathology remains a crucial area for future research.